2008
DOI: 10.1590/s0100-72032008000700006
|View full text |Cite
|
Sign up to set email alerts
|

Sintomas do trato urinário inferior três anos após o parto: estudo prospectivo

Abstract: ObjetivO: avaliar a freqüência de sintomas do trato urinário inferior (STUI) três anos após o parto em mulheres previamente entrevistadas no terceiro trimestre da gestação e comparar o impacto da gestação e do parto no desencadeamento dos STUI. Analisar o desconforto social e higiênico associado às queixas miccionais. MétOdOS: estudo prospectivo analítico. Em 2003, 340 gestantes foram selecionadas em um ambulatório de atendimento Pré-natal e responderam ao questionário pré-testado, com perguntas sobre STUI e d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
2
20

Year Published

2011
2011
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 0 publications
0
12
2
20
Order By: Relevance
“…Despite the fact that no statistically significant differences were found, the present study showed a slight predominance of UI among the primiparae, which disagrees with other studies performed in Brazil (14)(15)21) and in Europe (13 ) , which found that UI was more common among multiparae women. A study performed in Norway (3 ) , with 4,662 primiparae and 3,549 multiparae, found that parity is a strong risk factor for UI during pregnancy and that the UI prevalence is greater among women who have experienced childbirth.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Despite the fact that no statistically significant differences were found, the present study showed a slight predominance of UI among the primiparae, which disagrees with other studies performed in Brazil (14)(15)21) and in Europe (13 ) , which found that UI was more common among multiparae women. A study performed in Norway (3 ) , with 4,662 primiparae and 3,549 multiparae, found that parity is a strong risk factor for UI during pregnancy and that the UI prevalence is greater among women who have experienced childbirth.…”
Section: Discussioncontrasting
confidence: 99%
“…In literature, studies state that urinary incontinence affect up to 74% of the formerly continent pregnant women (10)(11)(12) . Considering a population of age between 17 and 45 years, studies show UI prevalence in the postpartum between 20% and 27.5% (10,(12)(13)(14)(15) .…”
Section: Introductionmentioning
confidence: 99%
“…Pesquisa que avaliou 120 mulheres, 3 anos após o parto, concluiu que a gestação, mais do que o parto, foi relacionada ao aparecimento da IUE, enquanto a urge incontinência foi significativamente maior após o parto 29 . Em outros estudos foi verificado que o número crescente de partos, especialmente o vaginal, pode desencadear a IU 25,30 , principalmente a IUE 8 .…”
Section: Discussionunclassified
“…Segundo Scarpa et al 5 57,5% das pacientes apresentaram IUE durante a gestação e 56,5% dessas tornaram-se assintomáticas até três anos após o parto.…”
Section: Introductionunclassified
“…As alterações anatômicas e funcionais do assoalho pélvico, que ocorrem durante o período expulsivo do parto podem regredir gradualmente, com restauro parcial ou completo do mecanismo da continência urinária 5 .…”
Section: Introductionunclassified